Technical Modernization of Station 3 Boiler Unit of Trypillia Thermal Power Station in Terms of Using Non-Standard Fuel - Oksana Yurasova; Mykhailo Semerak; Stepan Lys; Mykhailo Klub (Energy Engineering and Control Systems)
The research focuses on making flow and thermal calculations for the pulverized coal systems, pulverized coal feeding and combustion of gas coal in the TPP-210А boiler in order to develop major engineering solutions for converting the station 3 boiler to gas coal. It also aims to assess the temperature conditions of safe operation of the boiler heating surfaces, following the formulation of major engineering solutions. Based on the analysis of the options and experience of the technical modernization of the station 4 boiler, the process flow diagram for gas coal pulverization was constructed with the maximum use of the available equipment and in compliance with the effective fire and explosion hazard regulations. There were performed flow and heat calculations of the pulverized coal system for the selected option in the operation and start/stop modes with determining the drying capacity of the pulverized coal system and the range of pulverized coal rate for different coal grades. The coal-air mixture speed in the pulverized coal ducts and burner channels was calculated and recommendations for the adaptation of the existing burners for gas coal were formulated. The choice of the pulverized coal system for the station 3 boiler with the maximum use of the available equipment and in keeping with RD 34.03.352-89 (Explosion Hazard Regulations for Fuel Feed, Pulverized-Coal and Combustion Systems) and other regulatory requirements was substantiated.